KETIMPANGAN DISTRIBUSI PENDAPATAN RUMAH TANGGA MASYARAKAT DESA DI KECAMATAN PEUKAN BADA KABUPATEN ACEH BESAR - T. Makmur; Safrida Safrida; Kharisma Jayanthi (Jurnal Agrisep, 2011)
The Imbalance Level of Households Income Distribution in Sub district of Peukan Bada, Aceh BesarABSTRACT. The research aims to measure the imbalance level of households income distribution in the sub district of Peukan Bada, Aceh Besar. The method used is survey method. Sampling was conducted randomly and multi stage. The results were analyzed with gain ratio coefficient. It shows that the income distribution of households for those who work as farmer and local labor is categorized as moderate while that for those who work as civil employee and merchant is categorized as low. The calculation shows gain ratio index is 0.386 which lies on moderate category. Based on the World Bank criterion, it was found that 40% of the people with low income in this area have 11.4% of income per year. That means, the imbalance of income distribution in the sub district of Peukan Bada lies in a low level.